2011
DOI: 10.1186/1750-0680-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Historic emissions from deforestation and forest degradation in Mato Grosso, Brazil: 1) source data uncertainties

Abstract: BackgroundHistoric carbon emissions are an important foundation for proposed efforts to Reduce Emissions from Deforestation and forest Degradation and enhance forest carbon stocks through conservation and sustainable forest management (REDD+). The level of uncertainty in historic carbon emissions estimates is also critical for REDD+, since high uncertainties could limit climate benefits from credited mitigation actions. Here, we analyzed source data uncertainties based on the range of available deforestation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Forest carbon stock estimates have high variability. For example, investigations in Mato Grosso, Brazil, found a variability of more than two-fold in stock estimates (Morton et al, 2011). A review of studies estimating indirect LUC (iLUCs) associated with biofuel production found a large variation in estimates of forest carbon stocks among studies, contributing to the uncertainty in iLUC accounting (DG; Energy, 2010).…”
Section: Deforestationmentioning
confidence: 99%
See 1 more Smart Citation
“…Forest carbon stock estimates have high variability. For example, investigations in Mato Grosso, Brazil, found a variability of more than two-fold in stock estimates (Morton et al, 2011). A review of studies estimating indirect LUC (iLUCs) associated with biofuel production found a large variation in estimates of forest carbon stocks among studies, contributing to the uncertainty in iLUC accounting (DG; Energy, 2010).…”
Section: Deforestationmentioning
confidence: 99%
“…The size of the deforested area is another source of uncertainty. Brazil is considered to have one of the best monitoring programmes for deforestation, yet a 20% uncertainty in annual deforestation rate was found in the Mato Grosso study (Morton et al, 2011). Increased knowledge of LU after deforestation is vital as carbon losses for cropland are potentially higher than for pasture, perennial plantation or secondary forests (Morton et al, 2006).…”
Section: Deforestationmentioning
confidence: 99%
“…Time series of annual data on deforestation and understorey fires are, therefore, necessary to characterize the spatial and temporal relationships between forest conversion and understorey fires in standing forests. The nature of these relationships can inform efforts to Reduce Emissions from Deforestation and Forest Degradation plus enhance forest carbon stocks (REDDþ) [22,23], including whether understorey fires are an independent source of carbon emissions or a regional driver of deforestation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, intense drought episodes may compromise the consistency of the RRB comparison, between observed AGB and simulated total biomass, due to changes in carbon allocation patterns in vegetation (Doughty et al 2015). However, the AGB product in Liu et al (2015) also embodies significant uncertainties, that are partly related to the spatial extrapolation method (Mitchard et al 2014) based on Saatchi et al (2011). Moreover, this AGB dataset may be of limited use for evaluating impacts of climate extremes on tropical forests, in view of the possible underestimation of inter-annual variations of biomass by VOD signals, in comparison with other satellite indicators of vegetation (Liu et al 2011).…”
Section: The Rrb Concept Its Interpretation and Caveatsmentioning
confidence: 99%